Optimal fertilizer rates towards the improvement of nitrogen use efficiency and reduction of nitrogen export in paddy rice-wheat intensive farming - Legesse, Nebiyou; Sheng, Wu; Yao, Wang; Manqin, Gan; Peishi, Liu; Yu, Huang; Hongjun, Xu; HongXiang, Hu; Youhua, Ma (Frontiers in Environmental Science, 2023)
Fertilizer application above plant nitrogen (N) requirements, leading to N use inefficiency, has become the primary source of N surplus, posing nonpoint pollution threats. Chao Lake has received N loadings, primarily from the agroecosystem that surrounds it. Based on ten years of field monitoring and experiment, this study used optimum fertilizer rates (30% N reduction) to evaluate nitrogen use efficiency (NUE) and N export in the Chao Lake watershed of paddy rice-wheat rotational farming. Five treatments were tested, namely the Blank Treatment (CK), Conventional Fertilization Treatment (CFT), High Fertilization Treatment (HFT), Reduced Fertilization Treatment (CFT), Reduced Fertilization Treatment plus Straw addition (RFTS). The parameters employed to measure NUE were 1) by calculating NUE indicators; Agronomic efficiency (kg kg -1 ), recovery efficiency (%), and partial factor productivity (kg kg -1 ) 2) using the European Union NUE framework as a comparison tool. N export was measured using N export 1) Deleted[WPS_1688267195 [2]]:2 parameters, namely nitrogen loading (kg ha -1 yr -1 ), nitrogen runoff loss ratio (%), and net nitrogen runoff loss ratio (%).Results revealed that optimum N fertilizer input levels maintained high crop and biomass yields. The empirical model of y = y0 + a * exp (-0.5 * (x-x0)/b 2 ) explains the relationships between input N fertilizer and corresponding yield returns. Low yield responses to increased N input beyond certain limits were observed, which may lead to N accumulations. N export was much lower from the reduced fertilization treatments than other treatments. N export increased in ten years for both paddy rice and wheat seasons.Runoff volume influenced N export more than any other environmental factor studied.Overall, optimal fertilizer levels produced high NUE, maintained high economic yield, and produced lesser N exports; NUE was in the order of reduced > high > conventional fertilization treatments, while it decreased in ten years (2008 -2018) across all treatments. Such strategies that further reduce fertilizer levels by accounting for excess supplies are vital for consolidating effective N control measures.